Surveillance of Vibrio cholerae serogroups (O1 and O139) from surface and ground water sources in the Vhembe district, Limpopo province, South Africa - Kachienga, Leonard; Rikhotso, Mpumelelo Casper; Traore, Afsatou Ndama; Potgieter, Natasha (Frontiers in Environmental Science, 2024)
IntroductionVibrio cholera is increasingly emerging as a significant public health concern in developing countries. Choleragenic Vibrio cholerae O1 and O139 has reported to cause devastating disease and economic burdens in developing countries. In rural areas of the Vhembe district, most rivers and several communal boreholes are polluted as a result of sanitation issues around these water sources. The aim of this study was to determine the presence of choleragenic V. cholerae O1 and O139 in rivers and communal boreholes.MethodsThe analysis of physicochemical parameters and molecular techniques was used to establish the adaptation and detect the serogroups of V. cholerae in the water samples.Results and DiscussionThe results reported that electrical conductivities (EC) ranged between 18.78 and 154 μS/cm, with rivers such as Madandze and Mvudi recording >80 μS/cm, and those of the communal boreholes were ranged between 23.4 and 295 μS/cm, which were above the acceptable South African water quality guidelines of 0–70 μS/cm for rivers and communal boreholes. The results further revealed that most of the rivers detected positive for V. cholerae, except for the Mukhase river; the downstream points of Livuvhu and Nwedi rivers and the upstream point of the Nzhelele river; and several of the communal boreholes (Mak B1, B2, Kwe B3, 4, and 6) also tested positive for the presence of V. cholerae. The toxigenic Vibrios was also reported in Mutshundudi, Tshinane rivers, the upstream of Dzindi, Madanzhe, Nwedi, and the downstream of Sambandou rivers, as well as Mak B1, B2, and Kwe3 of communal boreholes. The serogroup O1 was detected on the Mutshundudi and Tshinane rivers, while serogroup O139 was detected upstream of the Dzindi, Madanzhe, Mutshundudi, and Tshinane rivers. There was also detection of the O1 serogroup in the communal boreholes (Mak B1 and Kwe B3), while O139 was only detected in one communal borehole (Mak B2). The development of robust policies, including an integrated water and sanitation safety surveillance web tool for monitoring water resources and public health protection, is required to make sure that drinking water in rural communities is safe for consumption.